A prolonged steroid therapy may be beneficial in some patients after the COVID-19 pneumonia. Issue 1 (1st January 2021) - Kostorz-Nosal, Sabina; Jastrzębski, Dariusz; Chyra, Michał; Kubicki, Piotr; Zieliński, Michał; Ziora, Dariusz
ABSTRACT: INTRODUCTION : This report introduces two cases presenting absorption of considerable radiological changes in the course of the coronavirus pneumonia in patients treated with prolonged oral steroids.CASES : The first case concerns a male receiving steroids only during hospitalisation in the Infectious Disease Hospital. After discharge, the patient experienced increasing dyspnoea resulting in hospitalisation in our Department of Lung Diseases. HRCT revealed progression of a bilateral, middle, and basal ground-glass opacity when compared to the examination performed at the early stage of the disease. The supplementary oxygen therapy and steroids were administered, followed by extended prednisone consumption up to 2 months after discharge. Follow-up HRCT revealed an almost complete absorption of the ground-glass opacity. The second case concerns a male treated with steroids only during hospitalisation in the Infectious Disease Hospital. Chest CT revealed widespread bilateral ground-glass opacities with consolidations. After discharge with no treatment, he suffered from severe dyspnoea and exercise intolerance, resulting in hospitalisation on the 7 th day of home stay. Since then, a continued steroid treatment was administered resulting in a clinical, spirometric, and radiological improvement.CONCLUSIONS : Based on these observations, patients after the COVID-pneumonia may derive benefits from a prolonged steroid treatment. Therefore, this class of medications should be considered in SARS-CoV-2 patients, especially in patients with persistent radiological changes and dyspnoea requiring the supplementary oxygen therapy. However, randomised controlled trials are required to establish guidelines for the steroid treatment in this group of patients.